Clinical application of mindfulness-oriented meditation in children with ADHD: a preliminary study on sleep and behavioral problems. Issue 5 (4th May 2022) - Zaccari, Vittoria; Santonastaso, Ornella; Mandolesi, Laura; De Crescenzo, Franco; Foti, Francesca; Crescentini, Cristiano; Fabbro, Franco; Vicari, Stefano; Curcio, Giuseppe; Menghini, 0000-0002-3459-2601Deny
Abstract: Objective: High incidence of sleep problems in children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD) has been described. Mindfulness meditation has emerged as a novel approach to sleep disturbances and insomnia remediation. This preliminary study tested the efficacy of Mindfulness-Oriented Meditation (MOM) training on sleep quality and behavioral problems in children with ADHD. Design: Twenty-five children with ADHD aged 7-11 years underwent two programs three times per week for eight-weeks: the MOM training (15 children) and an Active Control Condition (10 children). Main Outcome Measures: Objective and subjective measures of sleep quality and behavioral measures were collected before and after the programs. Results: Positive effects on sleep and behavioral measures were found only in the MOM group. Conclusion: Although they are preliminary, our results indicate that MOM training is a promising tool for ameliorating sleep quality and behavioral manifestations in ADHD.